2006
DOI: 10.1104/pp.106.085233
|View full text |Cite
|
Sign up to set email alerts
|

The BnALMT1 and BnALMT2 Genes from Rape Encode Aluminum-Activated Malate Transporters That Enhance the Aluminum Resistance of Plant Cells

Abstract: The release of organic anions from roots can protect plants from aluminum (Al) toxicity and help them overcome phosphorus (P) deficiency. Our previous findings showed that Al treatment induced malate and citrate efflux from rape (Brassica napus) roots, and that P deficiency did not induce the efflux. Since this response is similar to the malate efflux from wheat (Triticum aestivum) that is controlled by the TaALMT1 gene, we investigated whether homologs of TaALMT1 are present in rape and whether they are invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
174
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 213 publications
(188 citation statements)
references
References 52 publications
7
174
0
4
Order By: Relevance
“…The transcript of BnALMT1 and BnALMT2 was accumulated in the root, not shoot by Al in a concentration dependant manner. 20 This is similar to AtALMT1 19 but contrasts with TaALMT1 which is constitutively expressed in wheat and unaffected by Al treatment. 16 Our result also showed that neither BnALMT1 nor BnALMT2 is induced by P-deficiency.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The transcript of BnALMT1 and BnALMT2 was accumulated in the root, not shoot by Al in a concentration dependant manner. 20 This is similar to AtALMT1 19 but contrasts with TaALMT1 which is constitutively expressed in wheat and unaffected by Al treatment. 16 Our result also showed that neither BnALMT1 nor BnALMT2 is induced by P-deficiency.…”
Section: Introductionmentioning
confidence: 82%
“…16 Our result also showed that neither BnALMT1 nor BnALMT2 is induced by P-deficiency. 20 Therefore, we conclude that P-deficiency does not induce both BnALMT transcript accumulation and malate efflux in rape. 12,20 Overexpression of the BnALMT proteins in tobacco cells and Xenopus oocytes conferred an Al-induced malate efflux.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The Al-activated mechanism of malate exudation is well described in wheat (Delhaize et al, 1993;Sasaki et al, 2004), Arabidopsis (Hoekenga et al, 2006), Brassica napus (Ligaba et al, 2006), and rye (Collins et al, 2008), whereas the mechanism of Al tolerance in maize, soybean, sorghum, and barley involves mainly citrate release (Pellet et al, 1995;Yang et al, 2000;Magalhaes et al, 2007;Furukawa et al, 2007;Maron et al, 2010).…”
Section: Mechanisms Of Aluminum Tolerancementioning
confidence: 99%
“…It encodes a novel anion channel that controls the aluminium-activated efflux of malate from root apices. Homologous genes conferring similar functions have been isolated in Arabidopsis (Hoekenga et al 2006), rape (Brassica napus L.; Ligaba et al 2006) and rye (Secale cereale L.; Collins et al 2008). Interestingly, the genes controlling citrate efflux in response to aluminium stress are members of a different family named the multi-drug and toxic compound extrusion (MATE) family.…”
mentioning
confidence: 99%